Stochastic heating of charged particles in absence of first order resonances - Antonov, A.N.; Buts, V.A.; Kornilov, E.A.; Svichensky, V.G.; Kuzmin, V.V.; Tolstoluzhsky, A.P. (Вопросы атомной науки и техники, 2015)
Dynamics of charged particles in external electromagnetic fields in the absence of resonances proportional to the first degree of intensity of an electromagnetic field is investigated. Two schemes are investigated. In the first existence of several regular electromagnetic waves is supposed. It is supposed that frequencies and wave vector of these waves are such that the phase velocity one of beating waves is close to thermal velocity of particles. It is essential that thus organized Cherenkov resonances are proportional to square of small parameter (a square of dimensionless intensity of the field). In the second scheme is supposed that the phase of the field of wave changes by jump under the random law. Parameters of the studied systems at which one or other scheme of transmission of energy the field to particles has advantage are found. Досліджується динаміка заряджених частинок у зовнішніх електромагнітних полях при відсутності резонансів, які пропорційні першому ступеню напруженості електромагнітного поля. Досліджуються дві схеми. У першій передбачається наявність декількох регулярних електромагнітних хвиль. Передбачається, що частоти і хвильові вектори цих хвиль такі, що фазова швидкість однієї з хвиль биття близька до теплових швидкостей частинок. Істотно, що таким чином організовані черенковські резонанси пропорційні квадрату малого параметра (квадрату безрозмірної напруженості поля). У другій схемі передбачається, що фаза поля хвилі змінюється стрибком за випадковим законом. Знайдено параметри досліджуваних систем, при яких має перевагу одна або інша схема передачі енергії поля частинкам. Исследуется динамика заряженных частиц во внешних электромагнитных полях в отсутствие резонансов, пропорциональных первой степени напряженности электромагнитного поля. Исследуются две схемы. В первой предполагается наличие нескольких регулярных электромагнитных волн. Предполагается, что частоты и волновые векторы этих волн таковы, что фазовая скорость волн биения близка к тепловым скоростям частиц. Существенно, что таким образом организованные черенковские резонансы пропорциональны квадрату малого параметра (квадрату безразмерной напряженности поля). Во второй схеме предполагается, что фаза поля волны изменяется скачком по случайному закону. Найдены параметры изучаемых систем, при которых имеет преимущество одна или другая схема передачи энергии поля частицам.